PENGABDIAN PTMGRMD: IMPLEMENTASI POREST-1 SEBAGAI SOLUSI EFEKTIF PENGELOLAAN SAMPAH DESA CIHANJUANG, KECAMATAN CIMANGGUNG, KABUPATEN SUMEDANG - Fahmi, Rizal; Latuconsina, Hudaya; Lesmana, Sri Jaya; Sofian, Sofian (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Currently, waste management is one of the main challenges faced by various regions in Indonesia. Based on the results of field observations, Cihanjuang Village has experienced an increase in waste volume along with population growth, changes in community consumption patterns, lack of public awareness and not balanced with optimal waste management. This service aims to provide waste management solutions through education and innovation in space-saving waste management by providing the POREST-1 (Portable Rocket Echo Stove Incinerator) tool for the Cihanjuang village community, Sumedang Regency. The approach method used is Participatory Approach. The participants involved were all village staff, PKK mothers, posyandu cadres, hamlet heads, RT heads, RW heads and Karang Taruna of Cihanjuang village, Cimanggung sub-district, Sumedang Regency. The results of the program showed a significant decrease in waste volume and increased community awareness of the importance of sustainable waste management. In addition, the training provided succeeded in increasing the community's capacity to use and maintain the POREST-1 tool independently, which is expected to support the sustainability of this program in the future